Phytoplankton sinking rates in the Rhine region of freshwater influence - Peperzak, L.; Colijn, F.; Koeman, R.; Gieskes, W. W. C.; Joordens, J. C. A. (Journal of plankton research, 2003)
According to Stokes’ law, colony formation in phytoplankton would lead to enhanced sinking rates and higher sedimentation losses if colonies had the same densities as the phytoplankton cells they contain. In the Dutch coastal zone of the North Sea, algae settling out of the water column are subject to zoobenthos grazing or to physical mixing into the sediment and, therefore, the formation of colonies by common diatom species and the prymnesiophyte Phaeocystis globosa seems paradoxical: it would increase the probability that sedimentation becomes a significant loss factor. However, sinking rate measurements in the Rhine region of freshwater influence (ROFI) using SetCol settling columns did not reveal a straightforward relationship between phytoplankton sizes (<10 to >1000 μm) and sinking rates (–0.4 to >2.2 m day−1) of 24 autotrophic phytoplankton species and groups. In fact, under nutrient-replete conditions, the sinking rates of the diatoms Chaetoceros radicans, Rhizosolenia shrubsolei and Rhizosolenia stolterfothii decreased with size. The sinking rates of large colonies of the prymnesiophyte P. globosa were also negatively correlated with their size and positive buoyancy was observed. Chlorophyll a sinking rates exceeded 1 m day−1 periodically, which is sufficient to cause significant surface layer loss rates over 0.2 day−1. Under stratified conditions, both chlorophyll a concentrations and sinking rates in the bottom layer were significantly higher (+49% and +16%, respectively) than in the surface layer. These observations are discussed in relation to Stokes’ law, together with a critical analysis of the SetCol technique. It is concluded that: (i) SetCol gives adequate results when incubations are performed at or near in situ irradiance and temperature; (ii) sinking rates are predominantly determined by cell or colony density rather than their size; (iii) periodic sedimentation is an important species-specific loss process for phytoplankton in the Dutch coastal zone. It is speculated that for diatoms with low sinking rates, autolysis is an important loss factor.